Rapid acquisition of microorganisms and microbial genes can help explain punctuated evolution - Rosenberg, Eugene (Frontiers in Ecology and Evolution, 2022)
The theory of punctuated evolution posits that evolution occurs in rare bursts of rapid evolutionary change followed by long periods of genetic stability (stasis). The accepted cause for the rapid changes in punctuated evolution is special ecological circumstances, selection forces, brought about by changes in the environment. This article presents a complimentary explanation for punctuated evolution by rapid formation of genetic variants in animals and plants by the acquisition of microorganisms from the environment into microbiomes and microbial genes into host genomes by horizontal gene transfer. Examples of major evolutionary events driven by microorganisms include the formation of the first eukaryotic cell, the ability of some mammals to digest cellulose and other plant cell-wall complex polysaccharides, dynamics of root system architecture, and the formation of placental mammals and the first land plants. These changes were quantum leaps in the evolutionary development of biological complex systems and can contribute to an understanding of the mechanisms underlying punctuated evolution.